Adjuvant effects of a sequence-engineered mRNA vaccine: translational profiling demonstrates similar human and murine innate response. Issue 1 (December 2017) - Edwards, Darin; Jasny, Edith; Yoon, Heesik; Horscroft, Nigel; Schanen, Brian; Geter, Tanya; Fotin-Mleczek, Mariola; Petsch, Benjamin; Wittman, Vaughan
Abstract Background Prophylactic and therapeutic vaccines often depend upon a strong activation of the innate immune system to drive a potent adaptive immune response, often mediated by a strong adjuvant. For a number of adjuvants immunological readouts may not be consistent across species. Methods In this study, we evaluated the innate immunostimulatory potential of mRNA vaccines in both humans and mice, using a novel mRNA-based vaccine encoding influenza A hemagglutinin of the pandemic strain H1N1pdm09 as a model. This evaluation was performed using an in vitro model of human innate immunity and in vivo in mice after intradermal injection. Results Results suggest that immunostimulation from the mRNA vaccine in humans is similar to that in mice and acts through cellular RNA sensors, with genes for RLRs [ddx58 (RIG-1) andifih1 (MDA-5)], TLRs (tlr3, tlr7, andtlr8 -human only ), and CLRs (clec4gp1, clec2d, cledl1 ) all significantly up-regulated by the mRNA vaccine. The up-regulation of TLR8 and TLR7 points to the involvement of both mDCs and pDCs in the response to the mRNA vaccine in humans. In both humans and mice activation of these pathways drove maturation and activation of immune cells as well as production of cytokines and chemokines known to attract and activate key players of the innate and adaptive immune system. Conclusion This translational approach not only allowed for identification of the basic mechanisms of self-adjuvantation from the mRNA vaccine but also for comparison of the response across species, a response that appears relatively conserved or at least convergent between the in vitro human and in vivo mouse models.